Microbial Contamination and Meat Handling Practices in Hawassa City Butcher Shops, Ethiopia - Zebitu Kenaw; Amanuel Ejeso; Dawit Deresse; Beekam Kebede Olkeba (SAGE Publishing, 2024)
Background: Unsafe meat handling in butcher shops exacerbates microbial contamination, contributing to widespread food-related infections, particularly in developing countries like Ethiopia. In Ethiopia, microbial contamination in the meat supply chain is pervasive due to limited knowledge, inadequate hygiene practices, insufficient training, poor enforcement of food safety standards, and the absence of advanced diagnostic tools and regular microbial testing. This study aimed to assess the microbial load of meat, its contact surfaces, and meat handling practices of butcher shop workers in Hawassa city, Ethiopia. Methods: A cross-sectional study was conducted from March to April 2023 among butcher shop workers in Hawassa city, Ethiopia. One hundred forty-four (144) swab samples were collected, and the microbial load was evaluated by serial dilution method and counted using standard procedures. A total of 52 workers were interviewed to assess meat handling practices. Descriptive statistics were used to analyze survey and laboratory data. Results: The findings of this study revealed that the levels of Total Plate Count, Enterobacteriaceae , and staphylococci from meat samples collected from the butchers were 6.14, 5.58, and 5.23, respectively. The levels of Total Plate Count, Enterobacteriaceae , and staphylococci in the swab samples collected from knives, chopping boards, and weighing boards were 5.66, 5.27, and 5.28; 5.61, 5.33, and 5.03; and 5.29, 4.97, and 4.91, respectively. In the butcher shops, 83% of the meat was exposed to flies without protection, and 64% of meat handling equipment was not disinfected. Conclusions: The Total Plate Count, Enterobacteriaceae and staphylococci levels in meat samples and swab samples collected from knives, chopping boards, and weighing boards were above acceptable levels. These findings suggest the presence of potential pathogenic microorganisms, likely due to poor personal hygiene of the workers, inadequate cleaning and sterilization in the butcher shops, and cross-contamination from sources, including paper money handled, and skin contact.